Ernest Lapointe : Mackenzie King's great Québec lieutenant - Betcherman, Lita-Rose (Book collections on Project MUSE., 2002)
"In this long-overdue study of one of Canada's most important political relationships, Lita-Rose Betcherman details the close association between Ernest Lapointe and Prime Minister Mackenzie King and its effect on Canadian history." "Lapointe was the dominant French Canadian in federal politics from the start of the 1920s to the early years of the Second World War, serving as minister of justice and King's Quebec lieutenant. In return for promoting Liberal policies in Quebec, Lapointe was given an unusual amount of autonomy in his constituency, and, as the Prime Minister's understanding of both the province's sensibilities and its language were poor, Lapointe came to be relied upon to provide King with the French-Canadian perspective. Lapointe's role in maintaining Liberal party unity, and, by extension, national unity, was crucial. Equally important when it came to foreign affairs, he was known to take the lead over King, and the isolationist stance of both politicians served to undermine the League of Nations in its dealings with Italy over the invasion of Ethiopia." "Betcherman draws on key primary sources for her material, including the Lapointe Papers, the King Papers, the King Diary, and the media of the times. Ernest Lapointe thus documents Canadian politics and society in a rigorous and accessible manner that will appeal to both a scholarly and general audience."--Jacket